(untitled) (Profetik: Jurnal Komunikasi, 2016)
Gender stereotypes in television advertising have become a topic of a long debate, especially among media scholars. The case became a serious problem, because of gender bias ads will affect the way we think about the role and way of functioning of gender in society. This study describes how television commercials have given gender role stereotypes against women. It is becoming important to be studied further to see how people receive messages about gender norms. This study uses descriptive analytical method that aims to describe forms of stereotypical representations of women in television commercials. Research results obtained are in the advertising power generating imaging products has been taking part in cultivating stereotypes that have been embedded in women. Social symbols that had been attached to female and then processed further creatively by the advertisers to bring more products to be offered by the willingness of consumers. Products are offered in the form of soaps, detergents, Handbody, supplements are powerful medicine, food and other women always use the icon as a significant sales tool.